A systematic review and meta-analysis of the role of sugar-free chewing gum on Streptococcus mutans - Nasseripour, Melanie (BMC Oral Health, 2021)
BACKGROUND: Preventive strategies targeting Streptococcus mutans may be effective in reducing the global burden of caries. The aim of the current systematic review of published literature was to determine the difference in level of Streptococcus mutans in adults and children who chew sugar-free gum (SFG), compared with those who did not chew gum, who chewed a control gum or received alternatives such as probiotics or fluoride varnish. METHODS: Systematic review (PROSPERO registration No. CRD42018094676) of controlled trials with adult and child participants where chewing of SFG was the main intervention. Databases searched (1 Jan 1946 to 31 August 2020): MEDLINE, EMBASE, PsycINFO, Scopus, Web of Science, Allied and Complimentary Medicine Database, Cochrane Central Register of Controlled Trials (CENTRAL), Open Grey, PROSPERO and the Cochrane library of systematic reviews. ‘Search terms included Medical Subject Headings, and free text to cover the following range of constructs: chewing gum, sugar free, oral health, caries, xerostomia, periodontal disease. Data extraction and Risk of Bias assessment was undertaken by three researchers using a modified version of the Cochrane RoB tool (version 1). Data synthesis was conducted using meta-analysis in STATA. RESULTS: Thirteen studies of SFG with micro-organisms as outcomes were identified. The use of SFG significantly reduced the load of Streptococcus mutans (effect size − 0.42; 95% CI − 0.60 to − 0.25) compared to all controls. In seven of the 13 studies the confidence intervals of the effect size estimate included zero, suggesting no effect of the intervention. Twelve trials used xylitol gum only as the basis of the intervention; xylitol gum significantly reduced the load of Streptococcus mutans (effect size − 0.46; 95% CI − 0.64 to − 0.28) in comparison to all controls. There was a moderate level of heterogeneity across the included studies. No adverse effects were recorded. CONCLUSION: Chewing SFG reduces the load of Streptococcus mutans in the oral cavity in comparison to non-chewing controls. Considering the degree of variability in the effect and the moderate quality of the trials included, there is a need for future research exploring the use SFG as a preventive measure for reducing the cariogenic oral bacterial load. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12903-021-01517-z.